Isolation and Characterization of Gene Encoded Tonoplast Intrinsic Proteins from Halophyte Plant Salicornia herbacea - Netty Ermawati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Salicornia herbacea is a succulent halophyte plant which grows optimally under 300 mM NaCl. These plants may have acquired specific genes that are essential for tolerating salt. To obtain insight into the comprehensive molecular characteristics related to the salt tolerance mechanism, we performed a screening of salt-inducible genes in S. herbacea shoots by differential display. A comparative analysis of gene expression between control and salt-stressed conditions led to the detection of 6 cDNA clones induced by salt. Sequence analysis and database searching revealed that all of the clones have homology with tonoplast intrinsic proteins. We designated them as ShTIP1 to ShTIP6 (S. herbacea Tonoplast Intrinsic Proteins). One the identified genes, ShTIP6 showed higher induced under salt stress compared to other ShTIP genes. In this study, we characterized the expression of ShTIP6 in different organs and stresses.